Quo Vadis Diversifikasi Pendidikan Kebidanan Di Indonesia - Umi Sa'adatun Nikmah; Dian Agung Wicaksono (Pusat Penelitian dan Pengembangan Humaniora dan Manajemen Kesehatan, 2021)
The enactment of Law Number 4 of 2019 concerning Midwifery (Midwifery Law) provides its euphoria for the midwifery profession in Indonesia. The purpose of establishing the Midwifery Law is to improve the quality of midwives and midwifery services, provide protection and legal certainty to midwives and clients, and improve the health status of the community. Do the provisions in the Midwifery Law support the realization of these goals? This research tries to see whether the principle of clear objectives (beginsel van duidelijke doelstelling) as a material principle in the formation of the Midwifery Law has been manifested in the formulation of norms in the Midwifery Law, or other words whether the formulation of norms in the Midwifery Law supports the realization of the objectives of the formation of the Midwifery Law. This research specifically looks at the aspects of midwifery education as a starting point and a central point in improving the quality of midwives and midwifery services in Indonesia. This research is a qualitative study using the method of reviewing regulations and literature related to the regulation of midwifery education in Indonesia. As for normative legal research, it used a statutory approach. The results of the study indicate that the norms in the Midwifery Law, particularly related to midwifery education, are counterproductive with the aim of the formation of the Midwifery Law to improve the quality of midwives and midwifery services in Indonesia. Abstrak Berlakunya Undang-Undang Nomor 4 Tahun 2019 tentang Kebidanan (UU Kebidanan) memberikan euforia tersendiri bagi profesi bidan di Indonesia. Tujuan dibentuknya UU Kebidanan adalah untuk meningkatkan mutu bidan dan pelayanan kebidanan, memberikan pelindungan, dan kepastian hukum kepada bidan dan klien, serta meningkatkan derajat kesehatan masyarakat. Apakah pengaturan dalam UU Kebidanan mendukung terwujudnya tujuan tersebut? Penelitian ini mencoba untuk melihat apakah asas tujuan yang jelas (beginsel van duidelijke doelstelling) sebagai asas materiil dalam pembentukan UU Kebidanan telah diwujudkan dalam perumusan norma-norma dalam UU Kebidanan, atau dengan kata lain apakah perumusan norma dalam UU Kebidanan mendukung terwujudnya tujuan dibentuknya UU Kebidanan. Penelitian ini spesifik melihat aspek pendidikan kebidanan sebagai titik awal dan titik sentral dalam peningkatan mutu bidan dan pelayanan kebidanan di Indonesia. Penelitian ini adalah penelitian kualitatif dengan metode review peraturan serta literatur terkait pengaturan pendidikan kebidanan di Indonesia. Adapun sebagai penelitian hukum normatif, pendekatan yang digunakan adalah pendekatan peraturan perundang-undangan (statutory approach). Hasil dari penelitian mengindikasikan bahwa norma dalam UU Kebidanan, khususnya terkait pendidikan kebidanan, kontraproduktif dengan tujuan dibentuknya UU Kebidanan untuk meningkatkan mutu bidan dan pelayanan kebidanan di Indonesia.